Case report: Sepsis secondary to infected protracted parotid sialocele after maxillofacial oncologic surgery in a dog - Goldschmidt, Stephanie; Anderson, Jamie; Evenhuis, Janny; Stoopler, Eric; Sollecito, Thomas P. (Frontiers in Veterinary Science, 2024)
An 8-year-old male intact mix-breed dog was treated for a 3.7x3x3.6 cm grade 1 multilobular osteochondrosarcoma (MLO) arising from the dorsal aspect of the right coronoid process with a coronoidectomy, zygomectomy, and caudal maxillectomy. Ten months later, the dog presented for a swelling near the right angular process, which was presumed to be locoregional recurrence. Blood work and initial staging tests (abdominal ultrasound) had mild abnormalities of no clinical concern/significance. The dog was hospitalized with a plan for computed tomographic (CT) scan of the skull and chest to complete staging. Overnight, the swelling rapidly increased, the dog became laterally recumbent, febrile, and hypotensive. Laboratory evaluation revealed hypoglycemia, elevated lactate, and elevated band neutrophils with moderate toxicity, most consistent with sepsis. The dog was stabilized with fluid resuscitation, intravenous (IV) antibiotics, IV dextrose, and pressor support. Once stabilized, a contrast CT scan was performed which revealed evidence of an infected parotid gland sialocele. To our knowledge this is the first veterinary case that describes sepsis secondary to an infected protracted parotid sialoecele.Major maxillofacial oncologic surgery incurs multiple peri-operative risks including hemorrhage, infection, dehiscence, and functional complications. Yet, most are reported in the immediate perioperative period (0-3 months), with <2% being reported as short term (3-6 months), midterm (6-12 months), or long term (>12 months) sequela (1). Here we report an iatrogenic parotid sialocele developing 10 months following caudal oncologic surgery in a dog. Parotid duct stenosis and secondary dilation has been previously reported as a delayed complication in the veterinary literature occurring 2-3 years following caudal maxillectomy (2,3). In both previous cases, there were no secondary complications related to the salivary gland disease. In the